Promoting Development through Sustainable Wetland Management - Ipara , Hellen; Odwori , Paul; Mugalo , Irene (African Journal of Education,Science and Technology (AJEST), 2014)
Although wetlands are critical ecosystems that support diverse biological resources, functions and services, their integrity and sustainability are currently threatened by unsustainable human activities. This study was conducted around Marula swamp in Kenya. The study assessed how sustainable wetland management through local community involvement is promoting development. The study specifically investigated the role of Marula swamp in promoting conservation and local development; assessed strategies used to promote local community involvement in sustainable management of the swamp and its biodiversity; and determined threats facing the swamp and their impacts, measures adopted to mitigate the threats, and challenges faced in implementing the measures. The study targeted the local community living adjacent to the swamp and key respondents drawn from institutions located near the swamp, government ministries and departments, non-governmental organizations and community based organizations involved in its management, and local leaders. Sixty respondents among them fifty local community members and ten key informants were interviewed. Data was collected using structured questionnaires, discussions, personal interviews and field observation, and analyzed using descriptive statistics (frequencies and percentages) and chi-square test. Results revealed that Marula swamp is endowed with resources like medicinal plants (90%) and wildlife (80%). These resources are exploited for domestic use, sale, and to support local development. Benefits accruing from the swamp include water (100%) and herbal medicine (90%). Although various strategies are used to promote local community involvement in conserving and managing the swamp, they have not been effective (χ2=8.000, df=1, p=0.005) in promoting sustainable wetland management. Hence, threats arising from draining the swamp to create farmlands and burning swamp vegetation among others threaten the sustainability of the swamp. Awareness creation on the link between sustainable management of the swamp, improved livelihoods and development should be promoted through public education and extension, community meetings and other grassroots communication channels.